"Loving you": Use of metadiscourse for relational acts in WeChat public account advertisements. (October 2020) - Xia, Jie
Highlights: Use of metadiscourse in WeChat public account ads boasts its distinctive features. The function of metadiscourse can be elaborated by adopting pragmatic concepts. WeChat advertisers employed interactional metadiscourse to perform relational acts. Abstract: Social media advertising, with its interactivity, has become a critical site for brand-consumer relationship building. Recent work on its use for relational functions is primarily confined to the field of marketing, yet little attention has been paid to the linguistic devices that support relationship building on social media plarforms. In this paper, an empirical study is conducted on the use of metadiscourse in WeChat public account advertisements (hereafter WPA ads). Specifically, it examines how three interactional metadiscourse subcategories (engagement markers, self-mentions, and attitude markers) are used for relational acts in Chinese WPA ads. Analysis was conducted on 50 selected advertisements published in 2018 on the public WeChat accounts of five brands in different industries (mobile phone, laptop, tourism, electric appliance, and motorcar). The results indicate that engagement markers, self-mentions, and attitude markers, along with their distinctive linguistic devices, are used to perform the relational acts of directing, addressing, and expressing in WPA ads. This study extends the scope of metadiscourse research by investigating the use of metadiscourse in WPA ads while contributing to a more nuanced understanding of the interpersonal function of metadiscourse in WPA ads. It has implications for the technical writing of WPA ads, raising advertisers' awareness of how to employ metadiscourse to build solidarity with readers and manage their corporate image in an era of e-commerce. It also evidences the usefulness of applying a pragmatic concept to metadisocurse research, providing insight into how metadiscourse might be approached by drawing on notions from fields other than discourse analysis.